A review of the New Public Service model with knowledge management and cultural intelligence - De Angelis, Cristiano (Analecta política, 2024)
After the pandemic and the onset of wars, the economic crisis underscores the importance of integrating society into the relationship between state and market to enhance government action. To overcome this crisis, it is essential to understand that the effectiveness of public policies relies on shared governance, starting from the creation of a culture of knowledge and solution sharing with society, the private sector, the third sector, academia, international organizations, and evolved and developed countries. This paper not only reviews the literature on corruption, popular participation, knowledge management, and cultural intelligence but also presents the New Public Service (NPS) model as a foundation for a qualified popular participation model to reduce corruption, which several researchers attribute to the current New Public Management (NPM) model. This model illustrates that shared knowledge and solutions with society and other countries have the potential to transform national culture, thereby reducing corruption and enhancing the effectiveness of public administration projects.
Keywords: Corruption; Cultural Intelligence; Shared Governance; Cultural Change; Popular Participation